A prepandemic nutrition-sensitive social protection program has sustained benefits for food security and diet diversity in Myanmar during a severe economic crisis - Maffioli, Elisa M.; Headey, Derek D.; Lambrecht, Isabel B.; Oo, Than Zaw; Zaw, Nicholus Tint (Elsevier, 2023)
Background: One-third of preschool children in Myanmar were stunted in 2015–2016, and three-quarters of children 6–23 mo had inadequate diet diversity. In response, a large-scale nutrition-sensitive social protection program was implemented over 2016–2019. In 2020, however, Myanmar’s economy was hit hard by the COVID-19 pandemic and harder still by a military takeover in 2021. Objective: The objective of this study was to examine whether former beneficiaries of this program experienced better food security, food consumption, and diet diversity outcomes in the wake of major economic shocks. Methods: In a previous cluster-randomized controlled trial conducted over 2016–2019, pregnant women and their children aged <2 y were randomly assigned to either: 1) CASH; 2) CASH + social and behavioral change communication (SBCC); or 3) a control group. Subsamples of these former participants were then resurveyed 10 times from June 2020 to December 2021 during Myanmar’s protracted economic crisis. Randomized treatment exposure was used in a regression analysis to test for postprogram impacts on Food Insecurity Experience Scale indicators, household food consumption, and maternal and child diet diversity. We also examined the impacts on household income as a secondary outcome and potential impact pathway. Results: Both intervention arms reported lower food insecurity, more frequent consumption of nutritious foods, and more diverse maternal and child diets compared with households in the control group. However, the improved dietary outcomes were larger for mothers and children exposed to CASH+SBCC compared with CASH, as was their monthly household income. Conclusions: The findings suggest that a program combining cash transfers with nutrition-related education can yield sustained benefits 1–2 y after the program was completed. This strengthens the evidence to support the expansion and scale-up of nutrition-sensitive social welfare programs to redress chronic malnutrition and enhance nutritional resilience in the face of a severe economic crisis.